2018
DOI: 10.1002/bem.22126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate intensity static magnetic fields on osteoclastic differentiation in mouse bone marrow cells

Abstract: Although we recently demonstrated that static magnetic fields (SMFs) of 3, 15, and 50 mT stimulate osteoblastic differentiation, the effects of SMFs on osteoclastogenesis are still poorly understood. This study focused on the suppressive effects of SMFs on receptor activator of nuclear factor κB ligand (RANKL)-induced osteoclastogenesis and bone resorption. Direct SMFs inhibit RANKL-induced multinucleated osteoclast formation, tartrate-resistant acid phosphatase activity, and bone resorption in mouse bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…Much evidence from in vitro experiments, animal models, and clinical studies indicated that moderate SMFs have positive effects on bone metabolism [Yang et al, 2020; Zhang et al, 2014a]. Osteoblast differentiation can be promoted, and osteoclast differentiation can be inhibited by moderate SMF in vitro [Kim et al, 2017; Kim et al, 2018]. In animal models, moderate SMFs have been found to prevent and treat osteoporosis [Zhang et al, 2018a], promote fracture healing, repair bone defects [Aydin and Bezer, 2011; He et al, 2019], and mitigate osteoarthritis [Rogachefsky et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence from in vitro experiments, animal models, and clinical studies indicated that moderate SMFs have positive effects on bone metabolism [Yang et al, 2020; Zhang et al, 2014a]. Osteoblast differentiation can be promoted, and osteoclast differentiation can be inhibited by moderate SMF in vitro [Kim et al, 2017; Kim et al, 2018]. In animal models, moderate SMFs have been found to prevent and treat osteoporosis [Zhang et al, 2018a], promote fracture healing, repair bone defects [Aydin and Bezer, 2011; He et al, 2019], and mitigate osteoarthritis [Rogachefsky et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…The research on the use of HiSMF technology in magnetotherapy in clinics has been increasing due to its useful effects in many diseases, including cancers, edema, inflammation, wounds healing, and bone disorders [7][8][9][10]26]. Due to its safety and noninvasiveness, magnetotherapy has been approved as an instructive novel strategy by the US Food and Drug Administration (FDA) [16]. Especially, HiSMF has been considered as a regulator in bone metabolism, such as bone formation and bone resorption [27].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts play an important role in mediating calcium metabolism and bone resorption. SMF could mediate inhibition of osteoclastogenesis and bone resorption by Receptor Activator of Nuclear Factor-κ B Ligand-(RANKL-) induced Akt, GSK3β, MAPK, and NF-κB pathways by Kim et al [16]. Our previous works have revealed the vital role of HiSMF on osteoclasts, such as suppressing human preosteoclasts FLG29.1 cells survival and differentiation [17] as well as inhibiting NF-κ-Β ligandinduced osteoclastogenesis via mediating the iron metabolism of RAW264.7 cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that electric or magnetic fields of moderate strength inflicted the maximum inhibitory effects on organism performance [Newland et al, ; Hori et al, ; Kim et al, ; Wang et al, ]. For instance, static magnetic field (SMF) exposure at moderate intensity 15 mT maximally affected rat cell differentiation in vitro [Kim et al, ], and SMF exposure at 1 T increased cellular ATP levels in the rat, whereas 9 T decreased cellular ATP levels [Wang et al, ]. It is possible that herbivores exhibit a threshold of avoidance above some applied electrode voltages [Newland et al, ].…”
Section: Discussionmentioning
confidence: 99%